Is there an urban-rural-gradient in patients with urinary incontinence? - Wille, Sebastian; Katarzyna, Kawa; Ahrens, Ulrike; Eminaga, Okyaz; Engelmann, Udo; Jenny, Paas (Canadian Urological Association Journal, 2014)
Introduction: The objective of this study was to determine whether the responses to the same questionnaire differ between women living in a large city and women living in a rural area. Methods: We evaluated the medical records of 88 patients living in the large city of Cologne and of 86 patients living in Brühl and its surrounding rural regions. The responses on the International Consultation on Incontinence Questionnaire-Short Form (ICIQ-SF) of 88 patients who suffer from urinary incontinence and live in a large city were compared to the responses 86 patients who live the rural region of Brühl. In addition, ages, frequency of micturition, use of pads, prior and desired treatment were compared. Limitations of this study include its retrospective study design and the absence of sociodemographic data. Furthermore, the use of a pad test could objectify the extent of incontinence. Results: On average, patients from Cologne used of 6.2 pads and patients from Brühl used 3 pads. Patients from the large city scored 14 out of 21 points on the ICIQ-SF, and women from Brühl scored 11 out of 21 points. This difference was significant. Patients from Cologne had received medicinal treatment or physical therapy significantly more often. Conclusion: The results suggest that urinary incontinence is perceived as a greater impairment by patients residing in (large) cities compared to patients residing in rural areas. An urban-rural gradient in patients with urinary incontinence can be described.